2021
DOI: 10.1007/s12109-021-09797-7
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying Silenced Voices Through Micro- and Small-Press Publishing

Abstract: This research uses exploratory, mixed-method case studies to explore the relationship between Australian micro- and small presses (MSPs), their publishing and promotion of writers of difference (WODs), and the relationship to Couldry’s (2010) concept of voice . Through structured interviews with two publishing houses and their WODs, I (a) identified MSPs’ strategies for publishing and promoting silenced and neglected writers, thus facilitating the expression of voice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…An ICIRAS should reflect on findings of research from the sphere of Australian micro‐ and small presses. Professional Editor Jodie Lea Martire dug deeply into the publishing world: ‘The acquisition and editorial stages of publishing beg the question of who has the privilege and power to edit whom’ 55 . In order to support the voices of under‐represented authors, Martire found that the small presses cemented specific steps into their publishing processes.…”
Section: Why a Standard?mentioning
confidence: 99%
See 1 more Smart Citation
“…An ICIRAS should reflect on findings of research from the sphere of Australian micro‐ and small presses. Professional Editor Jodie Lea Martire dug deeply into the publishing world: ‘The acquisition and editorial stages of publishing beg the question of who has the privilege and power to edit whom’ 55 . In order to support the voices of under‐represented authors, Martire found that the small presses cemented specific steps into their publishing processes.…”
Section: Why a Standard?mentioning
confidence: 99%
“…Professional Editor Jodie Lea Martire dug deeply into the publishing world: 'The acquisition and editorial stages of publishing beg the question of who has the privilege and power to edit whom'. 55 In order to support the voices of under-represented authors, Martire found that the small presses cemented specific steps into their publishing processes. Therefore, all the steps of the rural research publication process should be examined to determine the points and pathways through which Indigenous peoples' voices are constrained or enabled.…”
Section: Amplifying Indigenous Peoples' Voices In Research Publicationsmentioning
confidence: 99%
“…Practitioner, scholarly and general accounts of contemporary publishing frequently settle on a normative, and oppositional, account of the literary marketplace. Global conglomerate publishing is perceived as in opposition to small and/ or independent publishing, with the former articulated as both dominating the marketplace and itself dominated by the forces of capital, their shareholders, and 'the market'; whereas independents or small press publishers are constructed as saviours of the uncommercial, the literary, and of 'culture' (examples of scholarly accounts include [22,32]). A practitioner example of this line of argument is articulated by Susan Hawthorne in Bibliodiversity: A Manifesto for Independent Publishing [15], in which she asserts that independent publishers provide 'a way of engagement with society and methods that reflect something important about the locale or niche they inhabit' (xi).…”
Section: Literary Cultural Policy and Sme Publishingmentioning
confidence: 99%